Understanding the response in Pugionium cornutum (L.) Gaertn. seedling leaves under drought stress using transcriptome and proteome integrated analysis - Wang, Ping; Wu, Zhaoxin; Chen, Guihua; Yu, Xiaojing (PeerJ, 2023)
Background Drought is one of the crucial constraints limiting horticultural plant’s production and development around the world. Pugionium cornutum is an annual or biennial xerophyte with strong environmental adaptability and drought resistance; however, the mechanisms with respect to response to drought stress remain largely unclear. Methods After seedling emergence, the gravimetric method was used to control soil relative water content (SRWC). Drought stress was applied to the six-leaf stage P. cornutum seedlings. The soil water content of different drought stress levels (L) was controlled by gravimetric method as follows: control (L1): 70–75% SRWC; moderate drought level (L2): 40–45% SRWC; severe drought level (L3): 30–35% SRWC, and the water was added to different drought stress levels at about 18:00 p.m. every day. The experiment ended when the leaves of P. cornutum showed severe wilting (10-leaf stage). Samples were harvested and stored at −80 °C for physiological determination, and transcriptomic and proteomic sequencing. Results Compared with L1, the leaves of P. cornutum seedlings were increasingly wilted after drought treatment; the SRWC of the drought-stress leaves decreased notably while the leaf water potential was rose; the proline, malondialdehyde (MDA) content increased with the continuous drought treatment but peroxidase (POD) activity decreased. Besides, 3,027 differential genes (DGs) and 196 differential proteins (DPs), along with 1,943 DGs and 489 DPs were identified in L2-L1 and L3-L1, respectively. The transcriptome and proteome integrated analysis manifested that only 30 and 70 were commonly regulated both in L2-L1 and L3-L1, respectively. Of which, 24 and 61 DGs or DPs showed the same trend including sHSPs, APX2, GSTU4, CML42, and POD, etc. However, most of DGs or DPs were regulated only at the transcriptome or proteome level mainly including genes encoding signal pathway (PYR1, PYLs, SnRK2J, PLC2, CDPK9/16/29, CML9, MAPKs), transcription factors (WRKYs, DREB2A, NAC055, NAC072, MYB and, HB7) and ion channel transporters (ALMT4, NHX1, NHX2 and TPK2). These genes or proteins were involved in multiple signaling pathways and some important metabolism processes, which offers valuable information on drought-responsive genes and proteins for further study in P. cornutum.
Keywords: Drought stress; Pugionium cornutum; Transcriptome; Proteome